PENGARUH PROGRAM BEHAVIOR BASED SAFETY TERHADAP TINGKAT PENURUNAN KECELAKAAN DI PT.INALUM KUALA TANJUNG - Nadiya Asvina; Arifuddin Muda Harahap; M. Bahri Al Soddik; Amalina Firdaus; Aldeo Nur Ahmad; Yuliza Anisa Fitri; M. Ramanda Alif Syaufi Ginting; Rahma Auliyah Nst; Kamelia Zahra Adilla; M. Rizky (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
The problem that often occurs in the world of work is that if a worker has a work accident at his company's place, what is the BBS function for worker safety at PT INALUM, then this problem is not enough to stop here, other problems also arise related to the company's SOP accountability for workers who had an accident at work in accordance with applicable law. With the implementation of the Behavior Based Safety program, it is hoped that the level of work accidents can be realized properly. In this study we used the sociological normative method. By collecting and analyzing an event systematically. The data we analyzed were obtained from various literature and laws and regulations.